Desecularisation and the 'faith agenda' in an era of austerity: their impact on women's and girls' rights in the UK. Issue 1 (2nd January 2017) - Dhaliwal, Sukhwant; Patel, Pragna
ABSTRACT: This article tackles the conjoined gender impacts of two state-led agendas in the UK – the 'faith agenda' and the 'austerity agenda'. We argue that the faith agenda has revisioned the relationship between the state and its citizens into a communitarian relationship mediated by religious organisations, while the austerity agenda has led to the withdrawal of state resources from key areas of social welfare provision and displaced responsibility for social welfare on to a growing number of unaccountable religious organisations. Together this has strengthened the position and role of conservative patriarchal religious leaders and organisations, while diminishing the secular spaces and resources available to women to exit violent and abusive situations, to access their rights in a range of fields from housing, social care, the law, and education, and impacted their ability to exercise full autonomy. In particular, this article highlights the issue of access to justice, and demonstrates that as the state rolls back funding and support structures for abused women and for legal aid in general, religious tribunals have gained prominence among state representatives and are stepping into spaces like marriage, family law, and child custody with devastating consequences for the safety and welfare of women and children.